Redefining the documentation of outdoor surface scatter scenes using geographic information systems - Pottage, Katie; Masters, Peter; Márquez-Grant, Nicholas (Wiley, 2025)
The field of forensic archaeology has been primarily associated with the search, location, and excavation of clandestine graves, and thus, other deposition types have been commonly neglected in research. Current literature typically addresses the use of traditional methods implemented for the excavation and recovery of human remains from clandestine graves but fails to provide the same for surface scatter scenes. This study aimed to explore the documentation of such scenes through the integration of traditional archaeological techniques, geophysical surveying techniques, and GIS. A mixed method study was created and utilized in three different simulated scatter scenes, allowing the qualitative and quantitative scope of GIS to be examined and assessed. The techniques were utilized successively and iterated until all simulated scenes had been documented. Within this study, terrain was the independent variable—this was nonrandomized and chosen to best suit sites where scatter scenes are most prevalent. Results demonstrated GIS to be an effective method in the documentation of contextual data at a forensic surface scatter scene, providing both qualitative and quantitative data. Such findings aid in understanding the admissibility of each technique in court and its impact on a case when presented as evidence. This research revealed that further exploration of surveying techniques in sites other than clandestine graves is necessary for forensic archaeology practice.
Keywords: 44 Human Society; GIS; dGPS; forensic archaeology; scatter scene; scene documentation; spatial analysis; surface deposition; total station; Legal & Forensic Medicine; 3199 Other biological sciences; 3499 Other chemical sciences; 4402 Criminology